Knowledge about COVID-19, coping and resilience in Mexican women: comparison by stress levels - Ana Leticia Becerra Gálvez; Alejandro Pérez-Ortiz; Yuma Yoaly Pérez-Bautista; Isaías Vicente Lugo-González; América Genevra Franco-Moreno; Erick Alberto Medina-Jiménez (Interacciones)
Background: The psychosocial effects derived from the COVID-19 pandemic have represented a challenge for the population worldwide. Stress is a frequent problem reported by women, impacting the strategies they use to deal with problems in daily life and their ability to recover from this critical phenomenon. Objective: The objective of this study was to evaluate the relationship between stress levels, knowledge about COVID -19, ways of coping, and resilience in women. Method: A non-experimental, cross-sectional, and correlational study was carried out in a group of 386 Mexican women through a format that was distributed on social networks. Results: The data suggest that the higher the level of knowledge about COVID-19, the greater the perceived stress. High stress is positively and statistically significantly related to coping style, denial (r = .245; q = .20) and cognitive-reflective analysis (r = .303; q= .21). Low levels of stress are negatively and statistically significantly associated with a weak effect size with factors like social competence (r= -.198; q= .11) and family support (r = -. 227; q = .16). Conclusion: Stress affects women considerably due to work overload and interpersonal factors. This study offers the possibility of knowing the emotional state of women in times of COVID-19.